Flavonoids exclusively present in mycorrhizal roots of white clover exhibit a different effect on arbuscular mycorrhizal fungi than flavonoids exclusively present in non-mycorrhizal roots of white clover - Scervino, J.M. (2005)
The flavonoids 5,6,7,8,9-hydroxy chalcone, 3,7-hydroxy-4′methoxy flavone, 5,6,7,8-hydroxy-4′-methoxy flavone and 3,5,6,7,4′-hydroxy flavone can be detected only in non-mycorrhizal roots of white clover, but not in mycorrhizal roots, whereas the flavonoids acacetin, quercetin and rhamnetin are only present in mycorrhizal roots. We tested the effect of several concentrations of these compounds on spore germination, hyphal growth, hyphal branching, formation of clusters of auxiliary cells and of secondary spores of the arbuscular mycorrhizal fungi Gigaspora rosea, Gigaspora margarita, Glomus mosseae and Glomus intraradices. Our results indicate that depending on the flavonoid, the tested compounds are involved at different stages in the regulation of mycorrhization. This hypothesis is strengthened by their differing effect on several AM fungal growth parameters. Furthermore, our study provides more data on the AM fungus genus/species specificity of flavonoids. © 2005 Taylor & Francis.